FABRIKASI MESIN CUP SEALER SEMI OTOMATIS DENGAN KAPASITAS 4 CUP - Abdul Hakim; Herru Santoso Budiono; Sigit Joko Purnomo (ELEMEN : JURNAL TEKNIK MESIN, 2026)
The rapidly growing packaging industry is driving the need for efficient technology for MSMEs. However, manual cup sealers on the market often result in loose seals and low productivity. This research aims to design and test a microcontroller-based, semi-automatic, 4-cup cup sealer to improve circuit neatness, system response, and seal quality stability. The method used is tool engineering through an experimental approach, encompassing literature review, design, manufacturing processes (welding, turning, assembly), and testing of temperature and time variations. Test results indicate optimal performance is achieved at a temperature of 180–185°C with a pressing time of 4 seconds. This machine has been proven to improve production efficiency and quality consistency, making it an affordable technological solution for MSMEs and a foundation for future production capacity development.